Sensitivity of Neuroimaging Indicators in Monitoring the Effects of Interferon Gamma Treatment in Friedreich’s Ataxia - Vavla, Marinela; Arrigoni, Filippo; Toschi, Nicola; Peruzzo, Denis; D’Angelo, Maria Grazia; Gandossini, Sandra; Russo, Annamaria; Diella, Eleonora; Tirelli, Stefania; Salati, Roberto; Rufini, Alessandra; Condo, Ivano; et al. (Frontiers in Neuroscience, 2020)
The identification of efficient markers of disease progression and response to possibly effective treatments is a key priority for slowly progressive, rare, neurodegenerative diseases for which no treatment is yet available such as Friedreich’s ataxia. Various imaging modalities have documented specific abnormalities in Friedreich’s ataxia that could be tracked to provide useful indicators of efficacy in clinical trials. Advanced MRI imaging (DTI, fMRI, rs-fMRI) and retinal imaging (OCT) were tested longitudinally in a small group of Friedreich’s ataxia patients participating an open label clinical trial testing safety and efficacy of 6 month treatment with interferon gamma. While DTI indices documented the slow progression of FA loss, fMRI and rs-fMRI were significantly modified during and after treatment. The fMRI changes significantly correlated with the SARA scale, used to monitor clinical response. OCT documented the known thickness reduction of retinal nerve fiber layer thickness but no change over time. This pilot study provides indications for the potential utility of fMRI and rs-fMRI as ancillary measures in clinical trials for Friedreich’s ataxia.